Mirror image: Recurrent Takotsubo cardiomyopathy with variable regional involvement - Lee, Mary; Fan, Jerry; Langsjoen, Dane; Giebel, Dan (SA Heart Journal, 2019)
Takotsubo cardiomyopathy (TCM), a stress-induced cardiomyopathy, is a well-recognised cause of left ventricular dysfunction. It commonly presents similar to acute coronary syndrome with chest, dyspnoea, and electrocardiographic changes consistent with ischaemia and elevations of cardiac markers. Takotsubo cardiomyopathy often presents with acute myocardial stunning without evidence of coronary artery disease or atherosclerotic disease that is out of proportion to the demonstrated disease. Takotsubo cardiomyopathy has characteristic left ventriculography and radiographic findings – including left ventricular hypokinesis, adjacent areas of hyperkinesis, and variable regional involvement (i.e. apical, mid-ventricular, or basal ballooning patterns). Recurrent disease can occur and is often found to have similar ventricular wall dysfunction patterns. However, we present an uncommon case of possible recurrent Takotsubo cardiomyopathy that was found to have variable regional involvement.